Potential pitfalls of computed tomography in advanced laryngeal cancer - Aslan, Hale; Pınar, Ercan; Öztürkcan, Sedat; Aladağ, İbrahim and Karaca Erdoğan, Nezahat and Etit, Demet and Demirkol Tuna, Bilge and İmre, Abdulkadir and Olgun, Yüksel and Ateş, Düzgün (ENT Updates, 2016)
Objective: In laryngeal cancer the most suspected regions of invasion are preepiglottic space (PES), anterior commissure (AC), thyroid cartilage (TC), subglottic region (SR) and extralaryngeal spread (ELS). The objective of this study is to compare the results of preoperative computed tomography (CT) with postoperative histopathologic analysis in these critical regions for the total or partial laryngectomy. Methods: Eighty-nine patients, who had undergone total laryngectomy with a diagnosis of laryngeal cancer reported that squamous cell cancer (SCC) between 2005 and 2013, were reviewed retrospectively. All the patients, after the first application done total laryngectomy before flexible laryngoscopy, computed tomography for the neck and endoscopic biopsy with direct laryngoscopy. Histopathological results of PES, AC, TC, ELS and SR invasion are compared to preoperative CT findings and determined of specificity, sensitivity, false negative and false positive results and rate of accuracy. Results: All the patients were male, median age was 67 (range: 48 to 81) years. Fifty-six patients were in T4 and 33 patients in T3 stage. Compared to results between positive CT findings and negative histopathological examination; PES invasion in 41 patients/ 5 patients, AC invasion was found in 38/ 15 patients, TC invasion in 28/16 patients, SR invasion in 49/ 9 patients and ELS invasion in 25 /7 patients. Accuracy rate of computed tomography in these regions are 85%, 64%, 76%, 79%, and 83%, respectively. All the results especially thyroid cartilage invasion were statistically significant. Conclusion: In all regions invasion, CT has a low diagnostic reliability in high-grade laryngeal cancer in our study. We suggested that histopathological results are the gold standard intraoperatively for determining total or partial laryngectomy.